Cooling and uplift history of the Niangniangshan granitic pluton in the Xiaoqinling goldfield, central China: Implications for tectonic evolution and gold mineralization. (23rd October 2019) - Wang, Yi‐Tian; Ye, Hui‐Shou; Ye, An‐Wang; Liu, Shu‐Lin; Hao, Jiao‐Long; Liu, Jun‐Chen; Wei, Ran; Huang, Shi‐Kang; Sun, Zheng‐Hao
Abstract : The Xiaoqinling Precambrian metamorphic terrane is located in the southern margin of the North China Craton, where it is the second largest gold‐producing province in China. The Huashan, Wenyu, and Niangniangshan granitic plutons are distributed from west to east across the Xiaoqinling terrane. To fully reveal the terrane's cooling and uplift history, a systematic thermochronological study of the Niangniangshan pluton was carried out in this work. Combined with previous data for the other two plutons, our new data allow us to draw four important conclusions: (a) The Niangniangshan granitic pluton has experienced three cooling–uplift stages, with a rapid stage from 141.7 to 118.5 Ma, a second slow stage from 118.5 to 40.3 Ma, and a final relatively rapid stage from 40.3 to 29.0 Ma. Correspondingly, the cooling rates are 17.24°C/Ma, 0.77°C/Ma, and 11.50°C/Ma. (b) The three plutons experienced similar post‐emplacement rapid cooling stages until ca. 120 Ma, with high cooling rates of about 17–20°C/Ma. Subsequently, their host terrane entered a long period of tectonic quiescence with cooling rates of less than 1°C/Ma. A new diachronous rapid cooling stage began first in the west at 57 Ma, then in the centre at 45 Ma, and finally in the east at 40 Ma with markedly different cooling rates. In this latter rapid stage, the Huashan and Wenyu plutons experienced a much more rapid cooling and uplift than the Niangniangshan pluton, resulting in the higher elevations and larger outcrop area of granitoids in the west and centre of the terrane than in the east. Consequently, the present topography of the Xiaoqinling terrane was close to present‐day form by the Eocene–Oligocene. (c) The emplacement of the three plutons was prior to the regional extension and detachment faulting in the Xiaoqinling terrane, with the evolution of magmatic thermal domes triggering development of the Xiaoqinling metamorphic core complex. (d) Gold mineralization of the Xiaoqinling goldfield took place at ca. 132–125 Ma, which was coeval with the early rapid cooling stage of the plutons and the extensional detachment faulting of the Xiaoqinling metamorphic core complex. Regionally, the gold mineralization overlaps lithospheric thinning and asthenospheric upwelling below the entire eastern part of the North China Craton that occurred during the major extensional regime in the late Early Cretaceous.